EMBEDDING ESG INTO CORPORATE LENDING DECISIONS VIA ESMS: EVIDENCE FROM UZBEK COMMERCIAL BANKS (American Journal of Business Management, Economics and Banking, 2026)
This study examines how Environmental, Social, and Governance (ESG) considerations can be embedded into corporate lending decisions through an Environmental and Social Management System (ESMS), drawing evidence from Uzbek commercial banks. The paper proposes an implementation logic in which ESG screening becomes a formal component of credit risk governance and complements traditional financial assessment. Empirical results indicate that ESMS was introduced in cooperation with ERM GmbH and the EBRD and institutionalized mandatory ESG screening for all new corporate loan applications above 10 billion UZS by the end of Q3 2024. The same evidence shows that seven projects potentially harmful to the environment were rejected and that ecological risks in the loan portfolio declined by 11%. The findings support the view that ESG integration is not merely reputational, but operationally actionable and measurable when embedded into credit decision workflows.